Novel Pt(IV) complex OAP2 induces STING activation and pyroptosis via mitochondrial membrane remodeling for synergistic chemo-immunotherapy - Renming Fan; Ruizhuo Lin; Shuo Zhang; Aohua Deng; Yongrui Hai; Junyan Zhuang; Yang Liu; Maosheng Cheng; Gaofei Wei (Elsevier, 2024)
Mitochondrial membrane remodeling can trigger the release of mitochondrial DNA (mtDNA), leading to the activation of cellular oxidative stress and immune responses. While the role of mitochondrial membrane remodeling in promoting inflammation in hepatocytes is well-established, its effects on tumors have remained unclear. In this study, we designed a novel Pt(IV) complex, OAP2, which is composed of oxaliplatin (Oxa) and acetaminophen (APAP), to enhance its anti-tumor effects and amplify the immune response. Our findings demonstrate that OAP2 induces nuclear DNA damage, resulting in the production of nuclear DNA. Additionally, OAP2 downregulates the expression of mitochondrial Sam50, to promote mitochondrial membrane remodeling and trigger mtDNA secretion, leading to double-stranded DNA accumulation and ultimately synergistically activating the intracellular cGAS-STING pathway. The mitochondrial membrane remodeling induced by OAP2 overcomes the limitations of Oxa in activating the STING pathway and simultaneously promotes gasdermin-D-mediated cell pyroptosis. OAP2 also promotes dendritic cell maturation and enhances the quantity and efficacy of cytotoxic T cells, thereby inhibiting cancer cell proliferation and metastasis. Briefly, our study introduces the first novel small-molecule inhibitor that regulates mitochondrial membrane remodeling for active immunotherapy in anti-tumor research, which may provide a creative idea for targeting organelle in anti-tumor therapy.